2021
DOI: 10.1186/s40945-021-00119-w
|View full text |Cite|
|
Sign up to set email alerts
|

Shoulder pain prevalence by age and within occupational groups: a systematic review

Abstract: Background Shoulder pain was previously shown to diminish in older populations and it was suggested that this could be explained by reduced usage with age. Our objectives were to investigate if estimates of shoulder pain continue to increase after the age of 50 in working populations and to compare these estimates in physically demanding occupations with sedentary occupations. Methods A systematic review of retrospective, cross-sectional, prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 47 publications
1
19
2
5
Order By: Relevance
“…In Table 3 : Results of individual studies, the individual results of the included studies are presented. In eleven studies a statistical negative impact was reported of video game playtime [ 3 , 5 – 7 , 9 11 , 13 , 14 , 16 , 17 ] on the musculoskeletal system. In four studies no impact was examined [ 2 , 4 , 8 , 12 ] and in one study no effect was found of video game playtime on the musculoskeletal system [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 3 : Results of individual studies, the individual results of the included studies are presented. In eleven studies a statistical negative impact was reported of video game playtime [ 3 , 5 – 7 , 9 11 , 13 , 14 , 16 , 17 ] on the musculoskeletal system. In four studies no impact was examined [ 2 , 4 , 8 , 12 ] and in one study no effect was found of video game playtime on the musculoskeletal system [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Watching TV is probably the most motionless undertaking of the screen-based activities, because it typically occurs in the evening time after dinner and a day of work [ 10 ]. Therefore, it is a kind of relaxing activity for most people [ 11 ]. Working at a computer, e.g., in the office on the other hand, often involves different kinds of sitting or standing positions, which are occasionally interrupted with short walks [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of shoulder pathology increases linearly with increasing age, however the prevalence of pain appears to decrease after the age of 65 [17]. This could be explained by the impact of physical activity and occupation on shoulder pain, a relationship which has been demonstrated elsewhere [18]. The global population is getting older and many countries are increasing their retirement age despite evidence that healthy working life expectancy is not increasing at the same rate [19].…”
Section: Summary Of Findingsmentioning
confidence: 96%
“…The term "chronic shoulder pain" refers to shoulder pain that has persisted for more than 6 months [6]. Chronic shoulder pain continues to be prevalent in older populations that are still working, particularly if their work is physically active or, at least, involves the use of their upper limbs [7]. Non-traumatic chronic shoulder pain refers to complications such as capsulitis, calcific tendinitis, glenohumeral joint arthritis, polymyalgia rheumatica, rheumatoid arthritis, supraspinatus tendinopathy or subacromial bursitis, rotator cuff tear, referred pain from mid or lower cervical dysfunction, radiculopathy from disc or osteophyte complex [8].…”
Section: Introductionmentioning
confidence: 99%